Diseño construcción de una máquina para perforar tuberías de petróleo - Jaramillo Correa, Christian Santiago (2016)
Currently the Hot Tap process is a fundamental work done in the oil industry, it helps to prevent problems that may arise in the flow lines. The study, selection, sizing, design and construction of a Hot Tap (hot cutting) machine used for drilling pipes when required a change of length or installation of a new line of flow is performed. The Hot Tap machine is developed through the projection planes, using current technological processes such as software design, among others, also it performs the selection of materials and design of each item. A hole of 44 mm in diameter is obtained, the size of the hole is defined by the pilot drill, the saw drill. The design of each element that makes up the Hot Tap machine, is made taking into account the operating conditions and performance. This machine is designed for exclusive use in oil drilling pipe, however in the oil field can extend its use as drilling in oil storage tanks.